PERANAN IKATAN NOTARIS INDONESIA (INI) TERHADAP PENGAWASAN NOTARIS DALAM PELAKSANAAN TUGAS JABATAN NOTARIS DI PROVINSI DKI JAKARTA - Stephanie .; Endang Pandamdari (Jurnal Hukum Adigama, 2018)
This study aims to determine the role of Indonesian Notaries Association (INI) to the supervision of Notary in the implementation of duties in the position of Notary in Special Region of Jakarta. Notary in performing his duties of office can not be separated from the code of ethics that has been established and must be implemented by every existing Notary. The Indonesian Notary Association (INI) as the only organization of Notaries certainly has an important role in the field of supervision. Special Capital Region of Jakarta as the center of government certainly has a greater chance in the case of a violation, in this case the violation of the code of ethics, such as disrespect and uphold the prestige and dignity of the notary so that more supervision and explanation of the Profession of Notary Profession. It takes proper supervision from the Indonesian Notary Association (INI) where in addition to the reprimand is also required strict sanctions that can give a deterrent effect for the Notary in violation, in order not to happen again the same mistake and the notary's good name is maintained. Indonesian Notary Association is expected to give an important role in this case for the development of Notary Indonesia especially in Special Capital Region of Jakarta.